Definitive, Defective or Deft? Reassessing Barth's Doctrine of Baptism in Church Dogmatics IV/4: Definitive, Defective or Deft? - McMaken, W. Travis (International journal of systematic theology, 2015)
Karl Barth's doctrine of baptism articulated in Church Dogmatics IV/4 is due for reassessment. Interpretation of this part of Barth's intellectual legacy has been conceptually determined by unresolved tensions within the Reformed tradition's sacramentology and by a widespread notion that Barth shifted from one side of this tension to the other over the course of his career. This article contests that notion and argues that Barth's doctrine of baptism is more sophisticated than often thought. By developing the concept of ‘paradoxical identity’ as a way to describe how Barth thinks about the relation between divine and human action, this article sheds new light on the value of Barth's work in Church Dogmatics IV/4.